Association between low-carbohydrate diet and chronic kidney disease in population with gestational diabetes mellitus history: based on the National Health and Nutrition Examination Survey database - Junli Zhang; Youlian Dong (Food & Nutrition Research)
Background: Gestational diabetes mellitus (GDM) is one of the most common metabolic complications during pregnancy, and is associated with a significantly increased risk of postpartum chronic kidney disease (CKD). Although a low-carbohydrate diet (LCD) is recommended for glycaemic management in GDM patients, its long-term impact on kidney health remains unclear. Objective: To address this knowledge gap, this study aimed to investigate the association between LCD and the risk of CKD in women with a history of GDM, providing evidence for optimising postpartum dietary intervention strategies. Method: GDM data from National Health and Nutrition Examination Survey database (2009–2018) were used, with LCD as an independent variable and CKD as a dependent variable. Univariate and multivariate logistic regression analyses were applied to investigate factors related to CKD. Stratified and sub-group analyses were conducted to investigate association of LCD with CDK. Restricted cubic splines (RCS) were utilised to analyse non-linear relationship between the two variables. Results: There were 701 samples in all (CKD: n = 130; non-CKD: n = 571). The LCD score and CKD risk were shown to have a significant positive association (Odds Ratio [OR] > 1, P < 0.05) in multivariate weighted logistic regression model. The link between LCD score and CKD was strongly impacted by race, body mass index (BMI), and smoking status (P for interaction < 0.05). In patients who presently smoke and use alcohol, stratified analysis showed a substantial positive correlation (P < 0.05) between LCD score and CKD risk. RCSs curve indicated a potential linear relationship (P-non-linear = 0.9561) between risk of LCD and CKD, with an LCD score of 10 serving as the criterion threshold for CKD risk and OR < 1 when LCD < 10, signifying a protective factor. Conclusion: Among women with GDM, higher LCD scores showed a significant positive correlation with CKD risk, particularly in sub-groups with smoking or alcohol consumption habits. The study suggests the need for careful evaluation of the long-term renal safety of LCD and highlights the importance of developing individualised dietary plans for high-risk populations.